FAPI-PET/CT in Cancer Imaging: A Potential Novel Molecule of the Century - Huang, Rong; Pu, Yu; Huang, Shun; Yang, Conghui; Yang, Fake; Pu, Yongzhu; Li, Jindan; Chen, Long; Huang, Yunchao (Frontiers in Oncology, 2022)
Fibroblast activation protein (FAP), a type II transmembrane serine protease, is highly expressed in more than 90% of epithelial tumors and is closely associated with various tumor invasion, metastasis, and prognosis. Using FAP as a target, various FAP inhibitors (FAPIs) have been developed, most of which have nanomolar levels of FAP affinity and high selectivity and are used for positron emission tomography (PET) imaging of different tumors. We have conducted a systematic review of the available data, summarized the biological principles of FAPIs for PET imaging, the synthesis model, and metabolic characteristics of the radiotracer, and compared the respective values of FAPIs and the current mainstream tracer 18F-Fludeoxyglucose (18F-FDG) in the clinical management of tumor and non-tumor lesions. Available research evidence indicates that FAPIs are a molecular imaging tool complementary to 18F-FDG and are expected to be the new molecule of the century with better imaging effects than 18F-FDG in a variety of cancers, including gastrointestinal tumors, liver tumors, breast tumors and nasopharyngeal carcinoma.